College chemistry - Harold Goldwhite (Harcourt Brace Jovanovich, 1984)
The book is designed as a tool to help student sharpen his problem-solving skills in chemistry. Each chapter covers a single topic, whose fundamental principles are broken down in outline form for easy reference. Each chapter also contains a Summary and a Raise Your Grades section, which give an opportunity to review the primary principles of a topic and the problem-solving techniques implicit in those principles. The solution to any problem in chemistry requires six procedures: 1) Understanding. 2) Analyzing. 3) Planning. 4) Executing. 5) Checking. 6) Reporting